Chronic Otomycosis Due to Malassezia Spp - Latha, R (Medknow Publications, 2010)
We report the case of a 31-year-old male presenting with complaints of mild pain in the right ear for three months and hypoacusis for 10 days. On otoscopic examination, a thin, papery, white material was extracted from his ear and sent for fungal identification. This material revealed presence of Malassezia spp – with characteristic “spaghetti and meat ball appearance”. The patient was treated with 2% acetic acid, hydrocortisone and Clotrimazole powder for one week and he resolved completely.